Designing the vertigo experience: vertigo as a design resource for digital bodily play - Byrne, Richard; Marshall, Joe; Mueller, Florian ‘Floyd’ (2016)
Vertigo can be described as an attempt to momentarily destroy the stability of perception and inflict a kind of voluptuous panic upon an otherwise lucid mind. Vertigo has, however, not been generally considered as a design resource and we believe it to be under-explored in the area of digital bodily play. To investigate how vertigo could be considered as a design resource in this context, we conducted a review of relevant literature and held a design workshop with nine students to explore the potential of vertigo as a design resource for digital bodily play. From our exploration we identify five key design themes that designers might consider when designing a Vertigo Experience. Through this work we hope to encourage designers of bodily play experiences to consider vertigo as a design resource in their games.